STRATEGI PEMASARAN DALAM PENINGKATAN PENJUALAN (STUDI PADA TOKO VAPORIZER LAMPUNG) - Rahmadi, M Dani; Aprilani, Deddy; Septiani, Winda (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2024)
This research aims to determine effective and efficient alternative marketing strategies to increase sales at Lampung Vaporizer stores. This research uses a qualitative approach with descriptive research type. The informants in this research were the Vaporizer Lampung shop owner, Vaporizer Lampung employees, and Vaporizer Lampung consumers. Data obtained using observation, interviews and FGD methods. The data analysis technique uses SWOT analysis. The results of this research show that the results of the SWOT diagram analysis show a position in quadrant 1, namely an aggressive strategy. The strategy that can be used is the S-O strategy, namely using the strengths you have and taking advantage of existing opportunities. Alternative strategies that Vaporizer Lampung can use to increase sales are increasing digital marketing such as maximizing social media, then utilizing e-commerce platforms, apart from that, Vaporizer Lampung has the alternative of opening branch stores to expand the market.